Peningkatan Keterampilan Berpikir Kritis Melalui Penerapan Model Pembelajaran Creative Problem Solving Pada Peserta Didik Kelas XI-IPA1 SMA Negeri 2 Masamba - Indrasari, Siti Zulfamia; Harnipa, Harnipa; Kadir, Fitriani; Akfar, Mariani; Rahmat, Dedy (Al-Khazini, 2021)
The objective of this research is to improve critical thinking skill of students class XI Science 1 at SMA Negeri 2 Masamba through creative problem solving learning model. This is a class action research by subjet of student of class XI. Science I at problem solving. Masamba of academic year 2015/2016 whiech consis 36 students.The result is show that (1) learning activities of students thaught by creative problem solving learning model have improvie from cycle I to cycle II (2) observation result of learning manegement by teacher on the cycle 1 and cycle II over 80% thus it is categorized is very good (3) the average (3) the average value of the results of the test of critical thinking skills of students has increased from the first cycle of 72 to 81 in the second cycle, (4) the thoroughness of the individual and the traditional skills of critical thinking of students has increased from 62.86% in the first cycle to 88.57 % in the second cycle.